Application to Coupled Fixed-Point Theorems on Complex Partial b-Metric Space - Gunaseelan Mani; Lakshmi Narayan Mishra; Vishnu Narayan Mishra; Imran Abbas Baloch; Manuel De La Sen (Journal of Mathematics, 2020)
In this paper, we prove coupled fixed-point theorems in complex partial b-metric space. The proved results generalize and extend some of the well-known results in the literature. We also give some applications of our main results.